2001
DOI: 10.1182/blood.v97.2.388
|View full text |Cite
|
Sign up to set email alerts
|

Cidofovir for cytomegalovirus infection and disease in allogeneic stem cell transplant recipients

Abstract: A retrospective study was performed to collect information regarding efficacy and toxicity of cidofovir (CDV) in allogeneic stem cell transplant patients. Data were available on 82 patients. The indications for therapy were cytomegalovirus (CMV) disease in 20 patients, primary preemptive therapy in 24 patients, and secondary preemptive therapy in 38 patients. Of the patients, 47 had received previous antiviral therapy with ganciclovir, foscarnet, or both drugs. The dosage of CDV was 1 to 5 mg/kg per week follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(43 citation statements)
references
References 29 publications
2
38
1
2
Order By: Relevance
“…Other authors have shown that this drug can be used safely with some precautions in kidney transplant and HSCT patients. 21,[39][40][41][42] In conclusion, we found a significant correlation in paediatric patients between BK virus replication in both urine and plasma with post-HSCT HC; moreover, a threshold with high specificity and PPV for HC was found by BK load determination. These data deserve further prospective investigation given the small sample size of our study and in view of the possible use of the BK load as a guide for a pre-emptive treatment strategy for HC.…”
Section: Discussionmentioning
confidence: 84%
“…Other authors have shown that this drug can be used safely with some precautions in kidney transplant and HSCT patients. 21,[39][40][41][42] In conclusion, we found a significant correlation in paediatric patients between BK virus replication in both urine and plasma with post-HSCT HC; moreover, a threshold with high specificity and PPV for HC was found by BK load determination. These data deserve further prospective investigation given the small sample size of our study and in view of the possible use of the BK load as a guide for a pre-emptive treatment strategy for HC.…”
Section: Discussionmentioning
confidence: 84%
“…32 Other antiviral drugs, including foscarnet, cidofovir and valganciclovir are also being studied for prevention of CMV disease. [33][34][35][36] As prophylactic and early treatment strategies aimed at further reduction of CMV antigenemia and disease are developed and tested, consideration should be given to comparison with high-dose acyclovir or valacyclovir in study designs.…”
Section: Discussionmentioning
confidence: 99%
“…Ljungman et al (55) performed a retrospective survey among 17 bone marrow transplantation centers and enrolled 82 patients who were treated with CDV for CMV disease (n ϭ 20) or for CMV reactivation (primary preemptive treatment, n ϭ 24; secondary preemptive treatment in patients who had failed or relapsed after previous preemptive treatment with another antiviral drug, n ϭ 38). The dosage was 1 to 5 mg/kg per week followed by maintenance treatment, and all patients received probenicid and prehydration.…”
Section: CDVmentioning
confidence: 99%